Impactos das transferências de renda governamentais no Mercado de trabalho brasileiro - Oliveira Filho, Sérgio Mendes de (2010)
In view of the empirical studies shortage in literature involving a possible reduction of labor as adverse incentive for the government income transference, this thesis intends to analyze in a detailed way the impact of transferences over the formal and informal labor supply from the family heads such as every individuals older than 10 years old. For the analyze of the effects in scope of the entrance decisions in job market it was estimated a multinomial logit model, while in the scope of the working time it was used a variation of the method of Durbin and McFadden (1984) for selection bias correction based on the multinomial logit, contained in Bourguignon et al. (2004). It has verified that transferences have positive effect over the probabilities that the individual doesn’t work and does informally work. However, this last one seems to be related to a substitution effect, once it has been observed a parallel negative effect over the probability to work on the formal sector. It has been obtained yet that the benefits negatively impacts on the offered hours by the family heads wether in the formal or non formal sector, effect that has happened to be verified on the hours offering in formal sector of all individuals. In the other hand, as we consider the hours of working of those who are engaged in informal sector, it has obtained that income transferences perform not as a discourage issue but as a magnifier factor of worked hours.